'Filmmaking is a hard thing to do': reflections on student and lecturer experience of Falmouth University's filmmaker in residence initiative. Issue 2 (4th May 2018) - Fox, Neil
ABSTRACT: This article outlines the rationale for and delivery of the pilot Filmmaker in Residence initiative at Falmouth University. The initiative led to the production of an award-winning independent feature film made by a professional and student crew from both within and external to the university. By supporting students to learn through an industry-based opportunity that took place within their educational setting rather than alongside it, the initiative sought to challenge a perceived practice/theory dichotomy by encouraging the students to engage with practitioners as educators and educators as practitioners. The initiative also sought to expose students to a different model of filmmaking than the high-end studio productions most familiar to them. The article explores the challenges and perceived successes of the initiative and draws on interviews with the students involved to explore their experiences. The article also outlines the key lessons learned, in particular, the value of offering industry opportunities to students early on in their film education that can inform and support their own assessment, the culture of the learning environment and their employability post-graduation.